2020
DOI: 10.1186/s13098-020-00566-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential roles of psychological and oxidative stress in insulin resistance: a cohort-based study

Abstract: Background: The present study investigated the relationships between psychological stress indices and oxidative stress marker, also when combined with emergent insulin resistance (IR), in the non-diabetic, middle-aged subjects, exposed to frequent/chronic psychological stressors. Methods: Cross-sectional data from a cohort of non-diabetic police officers (n = 234; 19F), aged 27-56 years, were used. Plasma inflammatory (CRP, TNF-α), oxidative stress (free 8-iso-prostaglandin F 2α ; 8-iso-PGF 2α) markers, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
5
0
2
Order By: Relevance
“…51 In the present study, glucose also contributed to the prevalence of hypertension, whereas the association of insulin resistance with hypertension had previously been highlighted. 21 Although large antioxidant supplementation trials, as pursued in the populations deemed exposed to high cardiovascular risk, exerted no mitigating effect on blood pressure, it was nevertheless demonstrated that the hypotensive effect of angiotensinconverting enzyme (ACE) inhibitors and Ang 1 receptor blockers was owed to inhibiting NADPH oxidase and decreased ROS production. 52,53 Oxidative stress might be a contributing factor, as neither genetic, nor behavioural factors, nor indeed psychological stress at large, are fully capable of conclusively explaining the actual pathomechanism of hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…51 In the present study, glucose also contributed to the prevalence of hypertension, whereas the association of insulin resistance with hypertension had previously been highlighted. 21 Although large antioxidant supplementation trials, as pursued in the populations deemed exposed to high cardiovascular risk, exerted no mitigating effect on blood pressure, it was nevertheless demonstrated that the hypotensive effect of angiotensinconverting enzyme (ACE) inhibitors and Ang 1 receptor blockers was owed to inhibiting NADPH oxidase and decreased ROS production. 52,53 Oxidative stress might be a contributing factor, as neither genetic, nor behavioural factors, nor indeed psychological stress at large, are fully capable of conclusively explaining the actual pathomechanism of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ROS stimulate a pro-inflammatory signalling pathway, linking oxidative stress with inflammatory state and also in insulin resistance and MetS. 18,21,57 In a stressful situation, both an ingestion of calories-rich foods, and anaboliccatabolic imbalance (high cortisol, insulin, low levels of the opposite hormones), may lead to oxidative stress, and systemic inflammation associated with MetS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in diurnal cortisol output have been implicated in the pathogenesis of both obesity [ 25 ] and T2D [ 26 ] in observational studies. While interrelationships between basal cortisol, chronic stress and components of the metabolic syndrome such as high adiposity and insulin resistance have been observed [ 27 ], it is possible that cortisol responses to stress elevate disease risk through other pathways [ 10 ]. Research is required to test this notion.…”
Section: Discussionmentioning
confidence: 99%
“…8-isoprostane-prostaglandin F 2α (8-isoPGF 2α ), a measure of lipid peroxidation, is widely considered to be the 'gold standard' biomarker of oxidative stress (Kadiiska et al, 2017;Roberts and Morrow, 2000). 8-isoPGF 2α is elevated in response to numerous environmental chemical and non-chemical stressors that may be reflective of a socioeconomic disadvantage, such as low educational attainment and smoking status (Cathey et al, 2021;Eick et al, 2018;Janczura et al, 2020;Ferguson et al, 2015a;van der Plas et al, 2019). Prior studies also suggest that certain biological factors, such as obesity, predispose individuals to elevated levels of 8-isoPGF 2α (Marseglia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%